Intergroup Toleration and Its Implications for Culturally Diverse Societies - Verkuyten, Maykel (Soc Issues Policy Rev, 2018)
In recent decades, tolerance has been proposed as a necessary response to the global rise in cultural and religious diversity. Tolerance is widely embraced in community, national, and international policies, in relation to many types of differences between people and groups. However, in both public and academic discourse, the notion of tolerance appears to have various meanings, which limits our ability to create, evaluate, and implement effective policies. To discuss various policy implications of toleration, we first consider the concept of toleration and its difference from prejudice. We then discuss existing research on intergroup tolerance, the importance of perspective taking, the asymmetry of tolerance, and the boundaries of toleration. Subsequently, we discuss research that indicates that the discourse of tolerance can function as a dimension of intergroup comparison that leads to acceptance or rejection of cultural and religious minority groups. Furthermore, we consider the depoliticized effects that tolerance discourse might have and the possible negative psychological consequences for groups that are tolerated in society. Gaps in existing knowledge are considered and policy implications are explored throughout.